Виявлення проблем оптимізації програмних систем в game dev індустрії та оцінка методів оптимізації таких проблем - Колесник, В. Ю. (ХНУРЕ, 2023)
This work highlights the main problems of game application optimization and methods of solving them. The criteria for evaluating the effectiveness of the proposed methods were considered, and the vector optimization problem was formed based on the obtained data. The solution of the problem gives an approximate estimate of the approximation methods relative to each other. On this basis, the developer can pre-assess what problems should be paid attention to, taking into account the specifics of his own project